Photocontrollable ambipolar transistors with π-conjugated diarylethene photochromic channels. (21st May 2019) - Kurokawa, Yuka; Hayakawa, Ryoma; Shimada, Shinya; Tanaka, Kouki; Higashiguchi, Kenji; Noguchi, Yutaka; Matsuda, Kenji; Wakayama, Yutaka
Abstract: Photocontrollable ambipolar transistors were developed by using diarylethene (DAE) layers with dibenzo[ b, d ]thiophene substituents as the transistor channels. An important feature is that both electron transport and hole transport occurred in the transistors upon ultraviolet (UV) light irradiation. The result indicates that the closed-ring isomer in the DAE molecules served as an ambipolar channel. Alternating UV and visible light irradiation controlled both the hole and electron currents, this was accompanied by photoisomerization from the closed-ring (semiconductor) to open-ring isomers (insulator). The light-induced on/off ratios in the drain currents were in the 95–225 range for the hole transport and in the 6–22 range for the electron transport. We found that the energy level alignment between the work function of the electrode and the molecular orbitals of the closed-ring isomer was responsible for the ambipolar transport. Our finding therefore offers a new strategy for developing optoelectronic organic transistors.